2011
DOI: 10.1242/dev.062208
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaMon2 couples Oskar-induced endocytosis with actin remodeling for cortical anchorage of the germ plasm

Abstract: SUMMARYDrosophila pole (germ) plasm contains germline and abdominal determinants. Its assembly begins with the localization and translation of oskar (osk) RNA at the oocyte posterior, to which the pole plasm must be restricted for proper embryonic development. Osk stimulates endocytosis, which in turn promotes actin remodeling to form long F-actin projections at the oocyte posterior pole. Although the endocytosis-coupled actin remodeling appears to be crucial for the pole plasm anchoring, the mechanism linking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 48 publications
1
53
1
1
Order By: Relevance
“…Given that Capu and Spir are actin nucleators that can directly regulate actin remodeling, they are likely to act downstream of Mon2 in the genetic hierarchy for pole plasm anchoring to the oocyte cortex. 16 We also found that the small GTPase Rho1, which forms a complex with Capu and Spir to regulate their actin nucleation activity, is highly concentrated at the oocyte posterior. 16 Furthermore, this posterior concentration of Rho1 requires Mon2, indicating that Mon2 might regulate the Capu/Spir activity to remodel cortical F-actin.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Given that Capu and Spir are actin nucleators that can directly regulate actin remodeling, they are likely to act downstream of Mon2 in the genetic hierarchy for pole plasm anchoring to the oocyte cortex. 16 We also found that the small GTPase Rho1, which forms a complex with Capu and Spir to regulate their actin nucleation activity, is highly concentrated at the oocyte posterior. 16 Furthermore, this posterior concentration of Rho1 requires Mon2, indicating that Mon2 might regulate the Capu/Spir activity to remodel cortical F-actin.…”
mentioning
confidence: 64%
“…13 This defect was also observed in rab5 mutant oocytes. 16 These data clearly demonstrated that the endocytic pathway is required for the anchorage of pole plasm components to the oocyte cortex ( fig. 2).…”
Section: Osk-induced Rearrangement Of F-actinmentioning
confidence: 76%
See 3 more Smart Citations